ABT-773: Pharmacokinetics and Interactions with Ranitidine and Sucralfate - Pletz, M. W. (American Society for Microbiology, 2003)
We assessed the pharmacokinetics and interaction of ABT-773 in 12 volunteers receiving ABT-773 alone or concomitantly with ranitidine or sucralfate. Data for 150 mg of ABT-773 were as follows: the maximum concentration of the drug in plasma (C(max)) was 318 ng/ml, its half-life was 5.66 h, and its area under the plasma concentration-time curve from 0 h to ∞ (AUC(0-∞)) was 1,662 ng · h/ml. Coadministration of ranitidine, reduced the C(max) (−25.7%) and AUC(0-∞) (−15.8%) significantly. Sucralfate had no impact on the bioavailability of ABT-773.